Safety of health workers during the COVID-19 pandemic and beyond: piloting WHO framework in Iran - Jafar Sadegh Tabrizi; Mondher Letaief; Hossein Mashhadi Abdolahi; Ramin Rezapour; Ahmed Alboksmaty; Mostafa Farahbakhsh (Journal of Health, Population and Nutrition)
Abstract Background Health Workers Safety (HWS) is a global health priority and essential at all times, in stable situations, in emergencies, in disease epidemics or pandemics. This study aimed to assess HWS during the COVID-19 Pandemic. Methods This cross-sectional study was conducted in 2022 in east Azerbaijan province, Iran. HWS was assessed based on 22 indicators suggested by WHO EMRO. We selected 15 PHC facilities and six wards from two hospitals randomly. Data collected (qualitative and quantitative) using national digital health records, staff records, and indicator-specific tools. In addition to measuring the indicator’s value, the indicators’ feasibility was also assessed. Descriptive and inferential statistics with SPSS-16 were used for data analysis. Results Totally, 325 Health Workers (HWs) (218 from PHC facilities and 107 from hospitals) participated in the study. Most of the participants in PHC facilities and hospitals were Community Health Workers (CHWs) (Moragheb Salamat) (45.4%) and nurses (37.38%), respectively. Most of HWs had completed the full vaccination schedule for Hepatitis B and COVID-19. Personal Protective Equipment (PPE) safety protocols were adhered by most of HWs within a healthcare facility. None of managers had attended nationally certified training for mental health support for health and care workers. Less than 20% of HWs participated in the work burnout prevention courses and most of HWs complained about work overload, or burnout. The job satisfaction level of hospital HWs (60.20%) was significantly higher than that of HWs from PHC facilities (57.18%) (P < 0.001). Conclusion Even though the mental health of HWs was not as expected, the indicators related to physical health and occupational health were at a suitable level. Also, there is not a system in PHC to audit the application of safety measures to mitigate the risk of contracting COVID-19. We recommend creating a specific system (precise and detailed) for HWs’ safety and applying safety measures in the PHC routine programs.